Qualidade da bebida de café de progénies resistentes a Hemileia vastatrix - Gomes de Souza, Antônio Carlos; Salustiano Pereira, Alonso; Martins Chaves, Geraldo (Revista Ceres, 2025)
Quality (flavor) characteristics of coffee samples from ‘Hibrido de Timor' and its progenies resistant to coffee rust, Hemileia vastatriz, were compared to those of commercial, standard varieties. The results were obtained through consumer and expert taste panels.